MelCher5k/BRAF+ subcutaneous human melanoma xenograft with CD20 expression - I. N. Mikhaylova; H. M. Treshalina; S. Sh. Karshieva; D. A. Khochenkov; N. V. Andronova; I. Zh. Shubina; M. V. Kiselevskiy (Успехи молекулярной онкологии)
Introduction. Metastatic melanoma of the skin (mMC) is characterized by an extremely unfavorable prognosis of survival. Significant remission of mMK is associated with the use of vemurafenib, which blocks the proliferation of cells with a mutation in the BRAF gene. However, after its cancellation, relapse develops rapidly, determining the need for continued treatment. The search for another therapeutic target in the primary mMC led to a small subpopulation of stem-like CD20 antigen-expressing cells. Pilot clinical trials of CD20-blocking rituxibam did not yield the desired result, which we interpreted as a lack of control of CD20 expression in recurrent cells, which is available only in vivo in an adequate human model of recurrent mMK / BRAF+ with high CD20 expression.Aim. To create an in vivo model of recurrent human mMC / BRAF+ with control of the representation of a subpopulation of cells with CD20 expression.Materials and methods. Vemurafenib (Roche, Switzerland), human melanoma cell culture MelCher5k / BRAF+, male Balb / c nude immunodeficient mice weighing 20–23 g breeding and maintenance at the N. N. Blokhin National Medical Research Center of Oncology were used. Mice with a transplanted tumor (n = 12) were divided into 2 groups: without the drug (control) and with the drug (vemurafenib). A comparative assessment of the growth dynamics of tumor nodes in the groups was carried out according to the volume ratio using the standard T / C (treatment / control) criterion, expressed as a percentage. The dynamics of the expression of S100, CD20, and CD45 markers was evaluated by flow cytofluorometry before the start of vemurafenib administration and at the end of follow-up.Results. According to the data obtained, in mice with MelCher5k / BRAF+ treated with vemurafenib from days 7 to 21, tumor reduction was observed from day 10 with complete remission by day 20. Relapses with the development of a tumor node at the implantation site (renewed growth of melanoma cells) occurred on day 28 (a week after drug withdrawal), and then the tumor progressed rapidly over the course of 34–41 days. In mice treated with vemurafenib, the proportion of CD20+ cells in the new focus was 35 %, which was 1.82 times higher than the proportion of CD20+ cells in the tumor of mice not treated with this drug (19 %). At the same time, the cells of the newly emerged tumor expressed the melanoma marker S100+ and did not express CD45.Conclusion. Thus, in vivo, using the MelCher5k / BRAF+ model, it was shown that in a recurrent tumor node developing after the use of vemurafenib, the proportion of stem-like cells expressing CD20 significantly increases. These data suggest that it is advisable to use the model to evaluate the clinical prospects of CD20-targeted agents capable of prolonging remission after vemurafenib withdrawal in patients with recurrent melanoma.